Improved MLVA typing reveals a highly articulated structure in Pseudomonas syringae pv. actinidiae populations. (April 2021) - Mazzaglia, A.; Turco, S.; Taratufolo, M.C.; Tatì, M.; Rahi, Y. Jundi; Gallipoli, L.; Balestra, G.M.
Abstract: Pseudomonas syringae pv. actinidiae (Psa) is the causal agent of the bacterial canker of kiwifruit, the most limiting disease of this cultivation worldwide. Since its first isolation and description in Japan in 1984, but especially after the pandemic started in 2008, the pathogen has been extensively studied. In the frame of intrapathovar genetic variability, five biovars have been identified and described. However, as for other bacterial pathogens, it is conceivable that a large part of the genetic diversity remains undiscovered, most likely in those areas where the pathogen and the host plant species have coevolved. Here, a Multi Locus VNTR Analysis (MLVA) assay based on 19 loci was applied to a comprehensive collection of 152 strains, representative of all the main infected areas in the world. Results were independently analysed by three different bioinformatic approaches and, besides representing a significant genetic variability between individuals, provided evidences for the presence of a conspicuous number of different populations within Psa. Some matches to the five biovars currently accepted, others seem to be somewhat related to them, but other ones emerge as completely independent. All but one of the fourteen identified populations are scattered throughout south-eastern Asia, five in China, six in Japan, and eight in Korea, with a substantial equilibrium in genetic richness among these countries; only representatives of the population corresponding to the biovar Psa3 are retrievable anywhere else in the world. The usefulness of this assay to thoroughly depict genetic variants of the pathogen is discussed. Highlights: Population structure of 152 worldwide kiwifruit bacterial canker strains was investigated. 19 Variable Number of Tandem Repeats loci were contemporaneously analysed. 3 different bioinformatic approaches were used to analyze the resulting dataset. The number of detected populations (14) exceeds the current biovar classification (6). Diversity is condensed in south-east Asia, whilst a single population is worldwide present.